Myelodysplastic syndrome in a case of new‐onset pancytopenia. Issue 3 (3rd March 2022) - Lancaster, Ian; Patel, Deep; Sethi, Vikas; Connelly, Weston; Namey, Joseph
Abstract: Myelodysplastic syndrome (MDS) is an infrequent cause of pancytopenia, which is a decrease in all three peripheral blood cell lines. We report the case of new‐onset pancytopenia following administration of a COVID‐19 vaccine and recurrent Zosyn use who was later found to have myelodysplastic syndrome. Abstract : Myelodysplastic syndrome (MDS) is a group of heterogeneous clonal hematopoietic stem cell malignancies. More than 100 genes have been found to be recurrently mutated in myelodysplastic syndrome, and these encode components of the spliceosome, chromatin remodeling factors, epigenetic pattern modulators, and transcription factors.